2006
DOI: 10.1080/10635150500433615
|View full text |Cite
|
Sign up to set email alerts
|

Medusozoan Phylogeny and Character Evolution Clarified by New Large and Small Subunit rDNA Data and an Assessment of the Utility of Phylogenetic Mixture Models

Abstract: A newly compiled data set of nearly complete sequences of the large subunit of the nuclear ribosome (LSU or 28S) sampled from 31 diverse medusozoans greatly clarifies the phylogenetic history of Cnidaria. These data have substantial power to discern among many of the competing hypotheses of relationship derived from prior work. Moreover, LSU data provide strong support at key nodes that were equivocal based on other molecular markers. Combining LSU sequences with those of the small subunit of the nuclear ribos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
407
6
13

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 348 publications
(462 citation statements)
references
References 63 publications
30
407
6
13
Order By: Relevance
“…This former view is borne out by our results showing strong support for Staurozoa as the sister group to Cubozoa plus Scyphozoa (Figures 5, 7) and is also in agreement with the topology of Zapata et al (2015), which had only weak support. Earlier phylogenetic analyses of rDNA and morphology also supported the view that Staurozoa is a distinct clade from Scyphozoa and Cubozoa, but instead suggested that Staurozoa was the sister group to the remaining medusozoans (Collins, et al 2006b;Van Iten, et al 2006).…”
Section: Resolving Key Controversies Within Medusozoamentioning
confidence: 65%
See 3 more Smart Citations
“…This former view is borne out by our results showing strong support for Staurozoa as the sister group to Cubozoa plus Scyphozoa (Figures 5, 7) and is also in agreement with the topology of Zapata et al (2015), which had only weak support. Earlier phylogenetic analyses of rDNA and morphology also supported the view that Staurozoa is a distinct clade from Scyphozoa and Cubozoa, but instead suggested that Staurozoa was the sister group to the remaining medusozoans (Collins, et al 2006b;Van Iten, et al 2006).…”
Section: Resolving Key Controversies Within Medusozoamentioning
confidence: 65%
“…Cnidarian phylogeny has been a source of debate for decades, with nearly every possible sister group relationship proposed among the major lineages of Medusozoa ( Figure 1) and Anthozoa ( Figure 2) (Collins 2009;Collins, et al 2006b;Daly, et al 2007;Stampar, et al 2014). Whole mitochondrial phylogenomic analyses have supported paraphyletic Anthozoa and Scyphozoa (Kayal, et al 2013;Park, et al 2012), but subsequent work suggested that these findings were due to saturation bias (Pratlong, et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within Hydrozoa (Cnidaria), an ancient phylogenetic divergence appears to have given rise to two primary clades with extant representatives, Trachylina and Hydroidolina (Collins, 2002;Collins et al, 2006a). In terms of species richness, the vast majority of hydrozoan diversity is contained within Hydroidolina (¼Leptolina sensu Schuchert, 2007).…”
Section: Introductionmentioning
confidence: 99%